The best place to read - Bertram, Debbie; Bloom, Susan (Susan Lynn); Garland, Michael, 1952- (New York : Random House, Inc., 2003)
A young child with a new book hunts inside and outside the house before finding the right chair for reading.
Keywords: Reading -- Fiction; Chairs -- Fiction; Mother and child -- Fiction; Stories in rhyme